An Algorithm for Improving Email Security on the Android Operating System in the Industry 4.0 Era - Isaac Moses Kisembo; Gilbert Gilibrays Ocen; Ocident Bongomin; Andrew Egwar Alunyu; Ildephonse Nibikora; Davis Matovu; Felix Bwire (Journal of Engineering)
The world is attesting a tremendous change today, which is remarkably coined as industry 4.0. With several technologies shaping industry 4.0 epoch, notably, its cybersecurity entails the security of communication and network operations activities. The most common form of communication in organisations and business today is electronic mails (email). One of the major threats to email communication is the lack of confidentiality for emails accessed via Android mobile devices due to the weaknesses of the Android operating system (OS) platform. In this study, an algorithm was designed and implemented on an Android application that allows an email sender to compose an email and set the time the email stays in the receiver inbox before it automatically wipes off. Primary data were collected from email users using tightly structured questionnaires and respondents comprised of those with email technical background and typical email users, while secondary data from scholarly journals and articles informed the study design. The designed algorithm was tested and evaluated through expert opinion. The result of the study indicates that the autowipe algorithm addresses the confidentiality issues and threats on Android email clients.